Выражение 1). a(a-+a)= 2). (m+8)^2-(m-2n)(m+2n)= 3). 3(b-10)^2+8b-5b^2= 4). (n+15)^2-n(n-19)= 5). 4c(9c-+1)^2= 6). (6-5m)(5m+6)+(5m-4)^2= !

ArkhamCity ArkhamCity    3   16.09.2019 07:40    0

Ответы
Okladakey Okladakey  07.10.2020 19:15
1). a(a-2b)-(3b+a)=a²-2ab-3b-a 

2). (m+8)^2-(m-2n)(m+2n)=m²+16m+64-m²+4n² = 4n²+16m+64

3). 3(b-10)^2+8b-5b^2=3b²-60b+300+8b-5b² = 300 - 52b -2b²

4). (n+15)^2-n(n-19)=n²+30b+225-n²+19n = 49n+225

5). 4c(9c-3)-(6c+1)^2=36c²-12c-36c²-12c-1 = -24c - 1

6). (6-5m)(5m+6)+(5m-4)^2= 36-25m² + 25m²-40m+16 = 52 - 40m
ПОКАЗАТЬ ОТВЕТЫ
Anastik222 Anastik222  07.10.2020 19:15
Решение смотри на фото
Выражение 1). a(a-+a)= 2). (m+8)^2-(m-2n)(m+2n)= 3). 3(b-10)^2+8b-5b^2= 4). (n+15)^2-n(n-19)= 5). 4c
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика